The extraordinary leader : - Zenger, John H. (McGraw-Hill, 2009)
When it was first published, this book attracted attention due to its use of scientific studies and hard data to demystify the concept of leadership. Now, consultants Zenger and Folkman revisit the subject to address leaders' most pressing concerns today, drawing on analysis of 200,000 assessments describing 20,000 managers. This edition has been updated to include the latest research into leadership psychology, and contains case studies for leading in a global environment. Zenger is a member of the HRD Hall of Fame. Folkman has written other books on leadership.